PHYSICO-MECHANICAL CHARACTERISTIC SOIL ON RESULT OF THE STEADY-STATE FLEXING ON OBJECT REKREATION PURPOSES IN CHERNIGOV (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of the study physico-mechanical characteristic soil by steady-state flexing on object recreation purposes on peninsula between r. Strizheni and r. Desna in Chernigov are stated. Keywords:flexing, resistance, friction, pile, density.